Prognostic value of ECG findings for total, cardiovascular disease, and coronary heart disease death in men and women. Issue 6 (1st December 1998) - De Bacquer, D; De Backer, G; Kornitzer, M; Blackburn, H
Abstract : Objective: To study abnormalities in the resting ECG as independent predictors for all cause, cardiovascular disease (CVD), and coronary heart disease (CHD) mortality in a population based random sample of men and women, and to explore whether their prognostic value is different between sexes. Design and subjects: An age and sex stratified random sample was selected from the total Belgian population aged 25 to 74 years. Baseline data were gathered and resting ECGs were classified according to Minnesota code criteria. The sample was then followed for at least 10 years with respect to cause specific death. Results are based on observations from 5208 men and 4746 women free from prevalent CHD at the start of the follow up period. Results: Although the prevalence of major abnormalities in general was comparable between sexes, women had more ischaemic findings, ST segment changes, and abnormal T waves on their baseline ECG, while men showed more arrhythmias, bundle branch blocks, and left ventricular hypertrophy. Fitting the multiplicative effect on subsequent mortality between all ECG classifications under study and sex indicated that the prognostic value of ECG changes was equal in women and men. Independently of other risk factors and other major ECG changes, almost all ECG classifications were significantly related to all cause, CVD, and CHD mortality. The most predictive ECG findings for CVD death were ST segment depression (risk ratio (RR) 4.71), major ECG findings (RR 3.26), left ventricular hypertrophy (RR 2.79), bundle branch blocks (RR 2.58), T wave flattening (RR 2.47), ischaemic ECG findings (RR 2.35), and arrhythmias (RR 2.15). The prognostic value of major ECG findings for CVD and CHD death was more powerful than well established cardiovascular risk factors. Conclusions: Abnormalities in the baseline ECG are strongly associated with subsequent all cause, CVD, and CHD mortality. Their predictive value was similar for men and women.